How strong are the links between new market conditions, new production principles, and better working conditions? - Nielsen, Klaus T (International journal of human factors in manufacturing)
This article reports on a study on how seven Danish small and medium-sized entreprises introduced parts of "just-in-time" in their production and especially how it influenced working conditions. Changes in skill demands and strains, as well as opportunities for autonomy and cooperation were investigated through primarily qualitative methods.